Principles of taxation for business and investment planning - Jones, Sally M.; Rhoades-Catanach, Shelley C. (McGraw-Hill Irwin, 2011)
Principles of Taxation for Business and Investment Planning, by Jones and Rhoades-Catanach, is a different approach to the study of taxation than the traditional tax return preparation approach. This book teaches students to recognize the role taxes play in business and investment decisions. In addition, the book presents the general role of taxation and its implications across all taxpaying entities before discussing the details relevant to specific entities. This approach allows students to really grasp the fundamental concepts that are the foundation for specific tax rules. The benefit is that the students will understand the framework of the tax system, even though specific tax rules and regulations change from year to year.